Pengaruh Kompensasi dan Dukungan Manajerial Terhadap Kepuasan Kerja Karyawan: Studi Kasus pada Karyawan CV. Indo Bata Beton - Maulana Abdul Rohman; Faizal Mulia Z; Nor Norisanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine the effect of Compensation and managerial support on employee job satisfaction at CV. Indo Bata Beton. The method used is a quantitative approach, including several linear regression tests and classical assumption tests. The sample size consists of 36 respondents. Data collection was conducted through questionnaires distributed to respondents, using a Likert scale of 1-5. Data analysis was performed using SPSS 27 software. The results of the study show that Compensation has a significant positive effect on job satisfaction of employees at CV. Indo Bata Beton, both partially and simultaneously, while managerial support does not significantly affect job satisfaction. However, Compensation and Managerial Support can predict the level of job satisfaction.